Analysis of antidiarrhoeic effect of plants used in popular medicine - Almeida Cybele E.; Karnikowski Margô G.O; Foleto Rejane; Baldisserotto Bernardo (Universidade de São Paulo, 1995)
People customarily use the extracts of plants known to have antidiarrhoeal effects without any scientific base to explain the action of the extract. For this reason, an investigation was undertaken with a view to determining the efficacy of the effects of the brute aqueous extract (BAE) of the leaves of Psidium guajava (guava), Stachytarpheta cayenensis (bastard vervain), Polygonum punctatum (water. smartweed), Eugenia uniflora (Brazil or Surinam cherry) and Aster squamatus (zé-da-silva) on the intestinal transport of water in rats and on the gastrointestinal propulsion in mice. With the exception of the BAE of S. cayenensis, all other BAE's have increased the absorption of water in one or more intestinal portion in relation to the control group. All tested BAE, except that of P. punctatum, reduced the gastrointestinal propulsion in relation to that of the control group. The results indicate that the BAE of the leaves of P. guajava, S. cayenensis, P. punctatum, E. uniflora and A. squamatus have a potential antidiarrhoeic effect to be confirmed by additional investigations in animals infected with enteropathogenic agents.